2012
DOI: 10.1088/1748-0221/7/01/c01005
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel designs of spark-protected micropattern gaseous detectors with resistive electrodes

Abstract: In the last few years many efforts have been made by various groups to develop sparkprotected micropattern gaseous detectors equipped with resistive electrodes instead of metallic ones. Great success has recently been achieved with resistive gas electron multipliers (GEMs), resistive micromesh gaseous structures and resistive Well/compteur a trou detectors. In this paper, we will focus on the development of a new family of spark-protected micropattern detectors: the 2D sensitive resistive microstrip counter an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
0
15
1
Order By: Relevance
“…Originally motivated by the need of reducing the sparking probability in another micro-pattern device, Micromegas [36,37], use of resistive electrodes to locally quench the formation of discharges has been developed also for GEM-like detectors as an alternative to multiple cascaded electrodes [38][39][40] F. Sauli / Nuclear Instruments and Methods in Physics Research A ∎ (∎∎∎∎) ∎∎∎-∎∎∎ devices (resistive plate chambers and the likes), the technical issue is finding a suitable process for producing stable and well controlled layers of high resistivity; the local voltage drop induced by the detected current affects also the efficient operation of the detectors at high radiation fluxes [41].…”
Section: Multi-gem Structuresmentioning
confidence: 99%
“…Originally motivated by the need of reducing the sparking probability in another micro-pattern device, Micromegas [36,37], use of resistive electrodes to locally quench the formation of discharges has been developed also for GEM-like detectors as an alternative to multiple cascaded electrodes [38][39][40] F. Sauli / Nuclear Instruments and Methods in Physics Research A ∎ (∎∎∎∎) ∎∎∎-∎∎∎ devices (resistive plate chambers and the likes), the technical issue is finding a suitable process for producing stable and well controlled layers of high resistivity; the local voltage drop induced by the detected current affects also the efficient operation of the detectors at high radiation fluxes [41].…”
Section: Multi-gem Structuresmentioning
confidence: 99%
“…The success of resistive GEMs triggered a series of similar developments, which are nowadays are being carried out by several other groups in the framework of the CERN RD51 collaboration [65]. As a result of these efforts it was demonstrated that the resistive electrode approach can be successfully applied to any micropattern gaseous detector and will make them robust and sparkprotected [16,66,67]. The latest designs of resistive micropattern detectors have segmented (on strips) electrodes [68].…”
Section: Rpc's New Family Members: Micropattern Gaseous Detectors Wit...mentioning
confidence: 99%
“…For this reason, in this paper, we focus on this more attractive approach, but to implement it we have modified the designs by manufacturing microdot structures on the top of a thick resistive GEM plate. [18], in which it was suggested to replace the parallel meshes with a resistive micro-hole microstrip detector. In this way, the light (or charge) multiplication region (strips) is geometrically shielded from the CsI photocathode.…”
Section: A Prototype Of a Dual-phase Lar Detector With A Csi Photocatmentioning
confidence: 99%